Some structural characteristics of mixed natural forest stand at a 10-year period in the Hyrcanian Region: Case study of Shourab Forest, Mazandaran Province, Iran (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Amiri M. 2019. Some structural characteristics of mixed natural forest stand at a 10-year period in the Hyrcanian Region: Case study of Shourab Forest, Mazandaran Province, Iran. . Biodiversitas 20: 950-955. This research was carried out in Shourab Forest in the Hyrcanian region, Northern Iran over a 10-year period (1996-2005) and data were analyzed based on systematic random sampling with permanent sample plots; 0.1 ha. The results revealed that n.ha-1 and v.ha-1 in study area increased from 126.3 and 245.2 in 1966 to 202.8 and 313.1 in 2006, respectively. The analysis of tree frequency in diameter classes at the first and the end of the period indicated un-even aged regular stands. The highest increase of number of trees was observed in 15, 20 and 25cm diameter classes, While the maximum change in volume per hectare, is related to the diameter classes 30, 65, 70 and 100cm. The regeneration values in most of the vegetation stages (except; 0-2.5cm) increased after a 10 years harvesting period. Development stages of this regeneration were seedling (53.4-53.3%), sapling (37.3-33.5%), thicket (6.8-10.4%) and small pole (2.5-2.8%), in 1996 and 2006, respectively. These conditions show that the selection method has been successful in our study area. The change in the utilization method of shelter-wood system to selection cutting method had been a positive impact on the quantitative forest condition after a 10-year period. In general, it can conclude that structural characteristics of mixed beech-hornbeam stands such as live trees dimension including tree height and diameter, number and volume of trees per hectare are different during the time. And eventually, the manipulation in the stands should be well timed and planned based on quantified structural properties of stands.